Effect of Light Emitting Diode (LED) Curing Modes on Depth of Cure (DoC) in BulkFill Composite Resin: an invitro study - Haji, Zainab; Ghafoor, Robia (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate the depth of cure in smart dentin replacement bulkfill composite resins polymerized by constant, pulse and ramped light-emitting diode curing modes. Method: The in vitro experimental study was conducted in November and December 2019 at the dental clinics of Aga Khan University Hospital, Karachi, and comprised cylindrical composite specimens 8x4mm in size which were polymerised in Teflon using light-emitting diode under constant mode in Group 1, pulse mode in Group 2 and ramped mode in Group 3. Once polymerised, each specimen was extruded from the mould and, using the International Organisation for Standardisation-4049 scrapping method, uncured resin was removed. Specimen lengths were measured with a Vernier calliper. Each specimen was measured thrice and the mean was taken as the depth of cure. Data was analysed using SPSS 24. Result: Of the 33 specimens, there were 11(33.3%) in each of the 3 groups. Mean depth of cure in Group 1 was 2.92±0.29mm, in Group 2 it was 2.88±0.27mm, and it was 3.18±0.26mm in Group 3. The difference between Group 2 and Group 3 was statistically significant (p<0.05). Conclusion: Maximum depth of cure of smart dentin replacement bulkfill composite was achieved by ramped cure mode of light-emitting diode unit, followed by constant and pulse modes. Key Words: Composite resin, Curing light, Surefil SDR flow, In vitro techniques.